2016
DOI: 10.5194/acp-2016-717
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

α-Pinene secondary organic aerosol yields increase at higher relative humidity and low NO<sub><i>x</i></sub> conditions

Abstract: <p><strong>Abstract.</strong> Secondary organic aerosol (SOA) yields from the photooxidation of α-pinene were investigated in smog chamber (SC) experiments at low (23–29 %) and high (60–69 %) relative humidity (RH), various NO<sub><i>x</i></sub>/VOC ratios (0.04–3.8) and with different aerosol seed chemical compositions (acidic to n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
5
0
1
Order By: Relevance
“…Specifically here, very high levels of IL-6 were observed post-exposure to pentadecane SOA formed under humid conditions. Prior studies reported opposing findings with some showing a significant effect of water on aerosol formation and chemical composition (Nguyen et al, 2011;Wong et al, 2015;Healy et al, 2009;Stirnweis et al, 2016), while others found little influence (Edney et al, 2000;Boyd et al, 2015;Cocker III et al, 2001). It is clear that humidity effects are highly hydrocarbon-dependent and further studies into the specific products formed under humid conditions are required to understand how these differences in chemical composition may translate to different cellular endpoints.…”
Section: Discussionmentioning
confidence: 79%
“…Specifically here, very high levels of IL-6 were observed post-exposure to pentadecane SOA formed under humid conditions. Prior studies reported opposing findings with some showing a significant effect of water on aerosol formation and chemical composition (Nguyen et al, 2011;Wong et al, 2015;Healy et al, 2009;Stirnweis et al, 2016), while others found little influence (Edney et al, 2000;Boyd et al, 2015;Cocker III et al, 2001). It is clear that humidity effects are highly hydrocarbon-dependent and further studies into the specific products formed under humid conditions are required to understand how these differences in chemical composition may translate to different cellular endpoints.…”
Section: Discussionmentioning
confidence: 79%
“…CC-BY 3.0 License. finding significant changes in SOA composition and yields (Nguyen et al, 2011;Wong et al, 2015;Healy et al, 2009;Stirnweis et al, 2016) and others reporting little difference (Boyd et al, 2015;Edney et al, 2000;Cocker III et al, 2001). Humidity effects are therefore highly hydrocarbon-dependent.…”
Section: ;mentioning
confidence: 94%
“…Similarly, anthropogenic precursors were chosen to include a long-chain alkane (pentadecane), a single-ring aromatic (m-xylene), and a poly-aromatic (naphthalene). These classes of compounds are emitted as products of incomplete combustion (Robinson et al, 2007;Jia and Batterman, 2010;Bruns et al, 2016) and have been shown to have considerable SOA yields (e.g., Chan et al, 2009;Ng et al, 2007b;Lambe et al, 2011). In addition to precursor identity, the effects of humidity (dry vs. humid) and NOx (differing peroxy radical (RO2) fates, RO2 + HO2 vs. RO2 + NO) on OP WS-DTT were investigated, as these conditions have been shown to affect the chemical composition and mass loading of SOA formed (Chhabra et al, 2010;Chhabra et al, 2011;Eddingsaas et al, 2012;Ng et al, 2007b;Loza et al, 2014;Ng et al, 2007a;Chan et al, 2009;Boyd et al, 2015).…”
mentioning
confidence: 99%
“…It is noted that for experiment 7 (isoprene SOA under RO 2 + HO 2 -dominant, "humid" conditions), experimental conditions deviated due to extremely low SOA mass yields. For this experiment, an acidic seed solution (8 mM MgSO 4 and 16 mM H 2 SO 4 ) was used under dry conditions to promote SOA formation via the IEPOX (isoprene epoxydiols) uptake pathway, which has a higher SOA mass yield compared to the IEPOX + OH pathway and contributes significantly to ambient OA (Surratt et al, 2010;Lin et al, 2012).…”
Section: Chamber Experimentsmentioning
confidence: 99%